EFFECT OF BACILLUS SUBTILIS CONCENTRATION AND FERMENTATION TIME ON THE QUALITY OF AFRICAN LOCUST BEAN CONDIMENT - Adesanya, Bose Joy; Faasema, Joseph; Acham, Israel Okpunyi (Bacterial Empire, 2021)
Fermented locust bean condiment in Nigeria has continued to attract low market value. This may partly be due to inconsistent quality of the product. In order to improve the quality of the condiment, there is need to explore standardization of the production process through use of starter culture such as Bacillus subtilis. Six samples were developed and were fermented at 35 °C in the laboratory using Bacillus subtilis concentrations of 1.0 mL and 1.5 mL at fermentation time(s) of 24 h, 48 h and 72 h respectively. The pH, microbiological, chemical and sensory attributes of the fermented locust bean condiment samples were analysed using standard methods and a ten member semi trained panelists on a 3 point hedonic scale. As the dose concentration of Bacillus subtilis increased with fermentation time, the pH and microbial load showed a corresponding increase; except at fermentation time of 24 h where the total viable counts of the fermented locust bean were insignificant to be counted. The peroxide, FFA and TBA values of the fermented locust bean condiment samples showed increases, while protein exhibited a decline in content. Bacillus subtilis concentration of 1.0 mL and a fermentation time of 48 h produced a condiment with higher degree of consumer acceptability with no unpleasant odour. The use of Bacillus subtilis concentration was found to be concentration and time dependent. Excessive fermentation activities of Bacillus subtilis were undesirable at 72 h as this gave rise to low quality locust bean condiment with unpleasant odour.